2023
DOI: 10.1039/d2fo03332a
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid supplementation alleviates hyperuricemia in high-fructose/fat diet-fed rats via promoting uric acid excretion and mediating the gut microbiota

Abstract: The prevalence of hyperuricemia (HUA) has been rising, which is typically accompanied by renal injury and intestinal flora disorder, leading to a non-negligible health crisis. Ferulic acid (FA), as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
2
6
1
Order By: Relevance
“…Both ferulic acid and p ‐coumaric acid reversed this effect, decreased URAT1 and GLUT9 transporter protein expression, and increased ABCG2 expression, alleviating hyperuricemia by reducing UA reabsorption and promoting UA excretion. This is consistent with previous studies that ferulic acid can alleviate hyperuricemia in vitro and in vivo (Zhang et al., 2023). Zhu et al.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Both ferulic acid and p ‐coumaric acid reversed this effect, decreased URAT1 and GLUT9 transporter protein expression, and increased ABCG2 expression, alleviating hyperuricemia by reducing UA reabsorption and promoting UA excretion. This is consistent with previous studies that ferulic acid can alleviate hyperuricemia in vitro and in vivo (Zhang et al., 2023). Zhu et al.…”
Section: Discussionsupporting
confidence: 94%
“…The hyperuricemia cell model was constructed by inducing HK‐2 cells with UA solution (Zhang et al., 2023). The cell concentration was adjusted to 8 × 10 4 cells/mL in a 96‐well plate (100 μL medium per well), maintaining the cells in logarithmic phase.…”
Section: Methodsmentioning
confidence: 99%
“…Astragalus membranaceus Bunge combined with S. miltiorrhiza Bunge can regulate the NF-κB/HIF-α signalling pathway, downregulate the expression of P65, p-P65, and HIF-1α, inhibit the mesenchymal transition of renal tubular epithelial cells, and reduce the deposition of extracellular matrix and collagen fibres, thereby delaying the process of renal interstitial fibrosis ( Qin, 2021 ). Research has shown that the main component of L. chuanxiong Hort, ferulic acid, can remodel the composition of the gut microbiota, characterized by an increase in beneficial bacteria (e.g., Lactobacillus and Ruminococcus ) and a decrease in pathogenic bacteria (e.g., Bacteroides ) ( Zhang et al, 2023 ). Although current research on these drugs as primary components of enema prescriptions is mainly based on oral administration, research on rectal administration is relatively scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Another highly meaningful study involved the administration of Ferulic acid (FA) to rats on a high fructose/high fat diet (HFFD). FA significantly reduced average serum uric acid levels, blood urea nitrogen, and creatinine levels ( 248 ). The expression of urate transport proteins was reduced, while that of secretory transport proteins increased in both the kidneys and intestines of the rats.…”
Section: Targeting Gut Microbiota Modulation For Metabolic Disorders ...mentioning
confidence: 99%
“…The expression of urate transport proteins was reduced, while that of secretory transport proteins increased in both the kidneys and intestines of the rats. FA was also found to mitigate renal oxidative stress, inhibit the activation of the TLR4/NF-κB pathway, and suppress the activation of downstream inflammatory response markers ( 248 ). Additionally, sequencing revealed that FA altered the composition of the gut microbiota, characterized by an increase in beneficial bacteria (e.g., Lactobacillus and Ruminococcus ) and a decrease in pathogenic bacteria (e.g., Bacteroides ) ( 248 ).…”
Section: Targeting Gut Microbiota Modulation For Metabolic Disorders ...mentioning
confidence: 99%